Nalisis Technology Acceptance Model Pada Koperasi Dan Ukm Menggunakan Sistem âOnlineâ Dengan Budaya Sebagai Variabel Moderator - Retnoningrum, Retnoningrum (Graduasi: Jurnal Bisnis & Ekonomi, 2014)
UKM and Cooperatives, business organizations in Indonesia, which is expected to alleviate the economic crisis. The issues that are currently of concern to theÂ  Government of Indonesia strive for economic recovery through by using of information technology. Tendency on the issue, the attitude of acceptance or rejection of a user information technology system (Technology Acceptance Model / TAM) is the technology acceptance model that can explain and predict ones intention to use the technology (behavioral intention) to use it ( behavior). The purpose of this study was to analyze the TAM model on UKM and cooperatives with an online system that culture moderated. Data was collected through surveys on UKM and Cooperatives in Surakarta. Data collected 145 respondents, using AMOS 18 shows that cultural variables masculinity/femininity moderate the perceived ease of use to the perception of use, as it also moderate the perception of the use of the intention to use technology systems, it is contrary to the uncertainty avoidance cultures. Both of these variables moderate the influence of intention ( behavioral intention ) toward usage behavior (behavioral ) use of information technology systems in UKM and cooperatives.